The Efficiency of the Load in Maximum Power Transfer Position - Pitri Bhakta Adhikari (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Electrical and electronic circuit systems are the basic foundations of modern science. These systems are the backbone of the conversion of electrical energy from small size as household appliances to the huge amount of innovation in the technological and industrial appliances. The maximum power transfer theorem is the fundamental principle of electrical circuit analysis, transfer of energy in this circuit with highest power. It further highlights the significance of understanding circuits in education and society, emphasizing the need for students to develop practical and theoretical knowledge. In the simple circuit diagram, the maximum power transfer theorem state that the load of the power is maximum when the load resistance is equal to the internal resistance of the circuit. The efficiency of the load is fifty percent in the circuit at which the power is maximum.